Potent and Selective Human Neuronal Nitric Oxide Synthase Inhibition by Optimization of the 2-Aminopyridine-based Scaffold with a Pyridine Linker - Wang, Heng-Yen (J Med Chem, 2016)
Neuronal nitric oxide synthase (nNOS) is an important therapeutic target for the treatment of various neurodegenerative disorders. A major challenge in the design of nNOS inhibitors focuses on potency in humans and selectivity over other NOS isoforms. Here we report potent and selective human nNOS inhibitors based on the 2-aminopyridine scaffold with a central pyridine linker. Compound 14j, the most promising inhibitor in this study, exhibits excellent potency for rat nNOS (K(i) 16 nM) with 828-fold n/e and 118-fold n/i, selectivity, with a K(i) value of 13 nM against human nNOS with 1761-fold human n/e selectivity. Compound 14j also displayed good metabolic stability in human liver microsomes, low plasma protein binding, and minimal binding to cytochromes P450 (CYPs), although it had little to no Caco-2 permeability.